Place: Towards a Geophilosophy of Photography : Towards a Geophilosophy of Photography - Shobeiri, Ali (Book collections on Project MUSE., 2021)
By examining photography through geography and philosophy, this book makes evident that place is not the content of a definite representation. To do this, it breaks down the participatory elements of photography into six tropes: the photographer, the camera, the photograph, the image, the spectator, and the genre. Afterwards, through a rigorous theoretical analysis of each of these themes vis-à-vis the notion of place, it shows how they manifest inactive, contingent, unlocalizable, liminal, evental, agential and exigent features. In doing so, it establishes a 'geophilosophy of photography', which regards place as that which resists being restricted to where it is (the photographer), to what it is (the camera), to where it goes (the photograph), to what it encloses (the photographic image), to how and when it occurs (the spectator), and to what it represents (the genre). Ali Shobeiri is Assistant Professor of Visual Art Theories in the Departments of Art History and Media Studies at Leiden University. He is co-editor of 'Animation and Memory' (2020).